Development of Threat Expression Following Infant Maltreatment: Infant and Adult Enhancement but Adolescent Attenuation - Junod, Anouchka; Opendak, Maya; LeDoux, Joseph E.; Sullivan, Regina M. (Frontiers in Behavioral Neuroscience, 2019)
Abstract Early-life maltreatment by the caregiver constitutes a major risk factor for the development of later-life psychopathologies, including fear-related pathologies. Here we used an animal model of early life maltreatment induced by the Scarcity-Adversity Model of low bedding (LB) where the mother is given insufficient bedding for nest building while rat pups were postnatal days (PN8-12). To assess effects of maltreatment on the expression of threat-elicited defensive behaviors, animals underwent odor-shock threat conditioning at three developmental stages: late infancy (PN18), adolescence (PN45) or adulthood (>PN75) and tested the next day with odor only presentations (cue test). Results showed that in typically developing rats, the response to threat increases with maturation, although experience with maltreatment in early infancy produced enhanced responding to threat in infancy and adulthood, but a decrease in maltreated adolescents. To better understand the unique features of this decreased threat responding in adolescence, c-Fos expression was assessed within the amygdala and ventromedial prefrontal cortex (vmPFC) associated with the cued expression of threat learning. Fos counts across amygdala subregions were lower in LB rats compared to controls, while enhanced c-Fos expression was observed in the vmPFC prelimbic cortex (PL). Correlational analysis between freezing behavior and Fos revealed freezing levels were correlated with CeA in controls, although more global correlations were detected in LB-reared rats, including the BA, LA and CeA. Functional connectivity analysis between brain regions showed that LB reared rats exhibited more diffuse interconnectivity across amygdala subnuclei, compared the more heterogeneous patterns observed in controls. In addition, functional connectivity between the IL and LA switched from positive to negative in abused adolescents. Overall, these results suggest that in adolescence, the unique developmental decrease in fear expression following trauma is associated with distinct changes in regional function and long-range connectivity, reminiscent of pathological brain function. These results suggest that early life maltreatment from the caregiver perturb the developmental trajectory of threat-elicited behavior. Indeed, it is possible that this form of trauma, where the infant’s safety signal or “safe haven” (the caregiver) is actually the source of the threat, produces distinct outcomes across development.